The effectiveness of alfalfa, nutrient model, and vegetative filter strips in reduction of nonpoint source pollution - Sullivan, Bailey Ann (Kansas State University, 2007)
Water quality in the United States needs to be improved. Currently, 42% (39% of rivers and streams, 45% of lakes and reservoirs) of monitored surface water is considered impaired, indicating that it is no longer suitable for its designated uses such as drinking, recreation, habitat, food supply, agriculture, and ground water recharge (USEPA, 2000, Carpenter et al., 1998). Nonpoint source pollution can be associated with animal manure. This project focuses on two sources of nonpoint source pollution. The first source is runoff from soils that have been enriched in nutrients (nitrogen and phosphorus) by manure application. This project evaluates how effective Alfalfa is at removal of nitrogen and phosphorus from nutrient enriched soils. It also evaluates the use of USDA’s Plant Nutrient model in association with nutrient management plans to prevent enrichment of soils. It was determined that Alfalfa is effective in reduction of nitrogen in soils; however, it was not feasible as a stand alone practice to remediate phosphorus. The use of USDA’s Plant Nutrient model indicated that Corn for silage is the most effective crop for reduction of soil phosphorus while alfalfa and the yields produced in 2004 was the most effective in reduction nitrogen. However, the model tends to underestimate soil nutrient uptake, so it is important to have soil tests conducted periodically to prevent nutrient deficiencies. The second source of nonpoint pollution discussed is runoff from animal feeding operations. This paper evaluates the effects of grass filter strips in prevention of pollution transport off of animal feeding operations. It was determined that filter strips with a ratio of runoff area to filter area of 1:2 is the minimum ratio to effectively prevent nonpoint source pollution.
Keywords: Animal feeding operations; Nutrients; Vegetation; Engineering, Agricultural (0539); Engineering, Environmental (0775)